Implementation of International Caries Classification and Management System (ICCMS™) Protocols in School-going Children for Control of Dental Caries: A Prospective Observational Study - Srishtee Singh; Richa Khanna; Rakesh Kumar; Rajeev K Singh; Afroz A Ansari; Vikram Khanna (Journal of South Asian Association of Pediatric Dentistry)
Aim and background: International Caries Classification and Management System (ICCMS™) is one of the most recent caries management pathways (CMP). Translation of ICCMS™ protocols to routine clinical practice, however, still needs evidence. Since control of disease should start early, pediatric population is most appropriate to be observed for such pathways. The study was hence planned to assess effect of ICCMS™ on control of dental caries in school-going children. Materials and methods: Study was planned as prospective observational for comparative effectiveness. Cohort of 50 participants (aged 5–9 years) with willingness to comply and at least some caries experience were observed for caries disease control domain for 1 year after being subjected to cyclic elements of ICCMS™. Clinical and radiographic investigations were performed at follow-up to determine disease control parameters and change in future likelihood of disease. Results: All initial and moderate lesions exhibited control at 12 months follow-up with only 5.8% of initial inactive lesions progressing. All initial active lesions were reversed. Only 8.3% moderate inactive lesions and 4.3% moderate active lesions progressed. Extensive inactive and active lesions were controlled by tooth-preserving operative care. New lesions were not observed on any sound surface. Disease likelihood changed at the end of 1 year for 25% of the total participants. Twelve point five percent participants showed a decrease in caries likelihood (z = −2.3664, p < 0.05). Conclusion: Control of dental caries was possible with implementation of ICCMS™ in school-going children. Advanced caries stages were more difficult to control than early stages, and early lesions were effectively reversed. Clinical significance of the study: The findings observed emphasize feasibility of implementation of ICCMS™ in school-going children with positive results of controlling dental caries in terms of lesion progression and also in terms of future likelihood of developing new carious lesions.